Punishment for Prostitution Offenders in the Review of Maqashid Syariah - Syarif, Muhammad; Zakaria, Zakaria; Zulhamdi, Zulhamdi; Hasbi, Husnaini; Nazir, Muhammad (Al-Hiwalah: Journal of Sharia Economic Law, 2024)
Prostitution which is prostitution is very dangerous for the maintenance of offspring (hifz al-nasl) and lead to criminal acts of crime under Islamic law. This library research was conducted by studying books and journals that are relevant to the writing of this article. In the Islamic perspective there is no nomenclature implicitly mentioning prostitution. Prostitution is the provision of sexual services by a man or a woman for money or satisfaction. Prostitution or prostitution is defined as adultery. Prostitution is a practice that destroys the foundations of family life, morality, morality, law and religion. In the Qur'an it is explained that the appropriate punishment for adulterymuhsan in the form of punishment of stoning and adulteryghairu muhsan was subject to a penalty of 100 lashes. Give punishment to the perpetrators of prostitution to prevent the occurrence of acts of adultery that can damage the sustainability of human life, especially aspects dharuriat, namely maintenance hifz al-nasl. Punishments are given in order to create sharia goals and punishment in Islamic law which includes prevention and guidance can be achieved and creates a deterrent effect for perpetrators, and not to repeat the act. Keywords: Punishment, Prostitutes, Maqashid Sharia